The Influence of Sex on Brain Development Genetics and the Possible Relationship with Sex-Dependent Differences in Psychiatric Disorders - Bağcaz,Arda; Terzi,Yunus Kasım; Şahin,Feride İffet (Gazi tıp dergisi, 2021)
There are sex-dependent differences in the prevalence, age of onset, and course of psychiatric disorders and cognitive abilities. Although it has been assumed that the direct effect of gonadal hormones in sensitive periods leads to sexually dimorphic brain development, current evidence suggests that another possible factor may be sex-specific regulations at the gene level. Understanding the sex differences at the gene level can be promising to identify the mechanisms that predispose or trigger psychiatric disorders, and may provide new prevention or treatment strategies. This paper aims to review the findings on the mechanisms that affect the sex-specific differences in brain development at the gene level and to discuss the relationship of these findings with different cognitive characteristics of the sexes and psychiatric disorders.